PENGARUH EARNING PER SHARE, CURRENT RATIO DAN INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE - Havisa Rahmania; Nafisah Nurulrahmatia (Jurnal Ilmiah Satyagraha, 2023)
Share price is an important consideration when assessing shareholder welfare andcan be used as an indicator of how well a company is performing. The higher thestock price, the higher the value of the company. Conversely, a low stock pricemeans that the value of the company will also be low. Low shares can mean thecompany's performance is not optimal. The author chose this title because he wasinterested in the problems that exist in the company. the problem with thecompany is the decline in stock prices in 2020. the value of current debt and netincome of food and beverage companies fluctuates. the purpose of this study wasto analyze the effect of EPS, CR, and inflation on stock prices. There are 7 companies listed on the Indonesian stock exchange in this study. This type ofresearch is associative. research instruments in the form of financial reports thatare accessed directly through the IDX website. based on the results of the analysisthere is the effect of EPE, CR and inflation simultaneously on stock prices seenfrom the calculated f value which is greater than f table. Partially, EPS has aneffect on stock prices, as seen from the t-count value which is greater than the ttable value. while CR and Inflation have no effect on stock prices because the tcount value is smaller than the t-table value.